A Study of Vitamin B12 Deficiency in Type-II Diabetic Patients on Metformin Therapy in Eastern Region of Nepal - Mishra, Gopal; Das , Pawan Kumar Lal; Karki, Dipesh (Medical Journal of Eastern Nepal, 2024)
Background Diabetes mellitus, a metabolic disorder marked by elevated blood glucose level, requires effective management to prevent complications. Metformin, a common frontline treatment for type -II diabetes, is linked to Vitamin B12 deficiency, which may trigger severe health disorders like anemia and neurological problems if remain undiagnosed for a longer duration. This study aims to assess the prevalence of Vitamin B12 deficiency among type 2 diabetic patients on metformin therapy. The objective is to assess the distribution of patients affected by this deficiency and understand how metformin therapy influences B12 levels among these patients. The Study was conducted at B&C Medical College Teaching Hospital and Research Center, Birtamod, Jhapa, Nepal. Methods A total of 200 diabetes patients on metformin were included in the study. Patients were included if they were diagnosed with type -II diabetes, were currently undergoing metformin therapy, and had been on the medication for at least 6 months. Data collected comprised patient age, gender, duration of metformin use, and serum vitamin B12 levels measured using chemiluminescence immunoassay (CLIA). Vitamin B12 deficiency was defined as serum levels <200 pg/mL, insufficiency as 200-300 pg/mL, and sufficiency as >300 pg/mL. Statistical analysis involved descriptive statistics and Chi-square tests. Results Out of the 200 diabetic patients taking metformin, 45% exhibited Vitamin B12 deficiency based on serum levels (<200 pg/mL), 30% had insufficient Vitamin B12 levels (200–300 pg/mL), and 25% had sufficient levels (>300 pg/mL) Deficiency rates were similar across genders but higher in patients over 47 years. A significant correlation was observed between longer metformin use and lower Vitamin B12 levels. Conclusion The results highlight a prominent rate of Vitamin B12 deficiency among diabetes patients prescribed metformin, especially in older patients and those on long-term therapy. Routine monitoring of vitamin B12 levels is recommended for these patients to prevent serious complications and improve health outcomes